Deciphering pathogenicity of variants of uncertain significance with CRISPR-edited iPSCs. Issue 12 (December 2021) - Guo, Hongchao; Liu, Lichao; Nishiga, Masataka; Cong, Le; Wu, Joseph C.
Abstract : Genetic variants play an important role in conferring risk for cardiovascular diseases (CVDs). With the rapid development of next-generation sequencing (NGS), thousands of genetic variants associated with CVDs have been identified by genome-wide association studies (GWAS), but the function of more than 40% of genetic variants is still unknown. This gap of knowledge is a barrier to the clinical application of the genetic information. However, determining the pathogenicity of a variant of uncertain significance (VUS) is challenging due to the lack of suitable model systems and accessible technologies. By combining clustered regularly interspaced short palindromic repeats (CRISPR) and human induced pluripotent stem cells (iPSCs), unprecedented advances are now possible in determining the pathogenicity of VUS in CVDs. Here, we summarize recent progress and new strategies in deciphering pathogenic variants for CVDs using CRISPR-edited human iPSCs. Highlights: CRISPR-edited human induced pluripotent stem cells (iPSCs) are a promising platform to determine the pathogenicity of genetic variants 'in a dish'. CRISPR-edited iPSCs provide a method for investigating the functions of a variant of uncertain significance with a more controlled cellular model and less variable results than clinical patient genome-wide association studies (GWAS). CRISPR-edited iPSCs have limitations with respect to examining variant-relevant phenotypes resulting from multiorgan phenotypes or cell–cell interactions. Future applications of CRISPR in iPSCs include determination of pathogenic variants for complex cardiovascular diseases by combining CRISPR screening and single-cell technologies.